(untitled) (Archives of Mechanics - Test, 1996)
The aim of this paper is to derive in a simple fashion the non-polynomial representations of a class of orthotropic functions in the two-dimensional case. Scalar-valued, vector-valued, symmetric and skew-symmetric tensor-valued functions of the second order have been considered.